2010
DOI: 10.1051/0004-6361/200913094
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-dynamic and chemical properties of the intra-cluster medium

Abstract: Aims. We aim to provide constraints on evolutionary scenarios in clusters. One of our main goals is to understand whether, as claimed by some, the cool core/non-cool core division is established once and for all during the early history of a cluster. Methods. We employ a sample of 60 objects to classify clusters according to different properties. We characterize cluster cores in terms of their thermo-dynamic and chemical properties and clusters as a whole in terms of their dynamical properties. Results. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
98
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 117 publications
(133 reference statements)
13
98
0
Order By: Relevance
“…Our results are consistent with the discussion in Leccardi et al (2010). The non-cD clusters in this paper include merging clusters in various stages, from heavily distorted morphologies to relatively relaxed ones without cool cores.…”
Section: Mixing Of the Icm In Non-cd Clusterssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with the discussion in Leccardi et al (2010). The non-cD clusters in this paper include merging clusters in various stages, from heavily distorted morphologies to relatively relaxed ones without cool cores.…”
Section: Mixing Of the Icm In Non-cd Clusterssupporting
confidence: 92%
“…Leccardi et al (2010) found that some medium-and high-entropy core systems have central abundance excess, most of which are undergoing a phase of rapid dynamical changes, and suggested that these clusters originate from low-entropy core systems.…”
Section: Mixing Of the Icm In Non-cd Clustersmentioning
confidence: 99%
“…Leccardi et al 2010;Baldi et al 2012b). The data points are plotted as function as radius and redshift, separating between CC and NCC systems, in Fig.…”
Section: Results On the Spatially Resolved Abundance Evolutionmentioning
confidence: 99%
“…The fraction of CC objects would then be computed from the subsample and not from HIFLUGCS. At variance with the cores, it has been found that in cluster outskirts the surface-brightness profiles are essentially self-similar (Neumann 2005;Croston et al 2008;Leccardi et al 2010), so the selection based on the fluxes in the outer regions should be unbiased. We define a new sample by selecting those objects for which the flux in an annulus excluding the core, and not the total flux, is above a given flux limit.…”
Section: Selection Of the Subsamplementioning
confidence: 99%